Narrative Strategy of Paul Verlaine’s Prose Poems - Bigun, Olga (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article analyses historical and genetic origins of the genre of prose poem. It singles out the genus-genre syncretism of prose poem, the foundation of which lies in the intertwining and interpenetration of epic, dramatic and lyrical principles, "overlapping" of different modifications. The material under study is represented by a collection of prose poems by Paul Verlaine Les mémoires d'un veuf. The aim of the article is to study the narrative peculiarities of a prose poem given the syncretic nature of the genre, and its delivery, which allows to analyze artistic works from the standpoint of their composition and structure. According to the internal genre-style dominant, three forms of narrative modeling are distinguished: a narrative with the predominance of epic-realistic elements, a narrative with the predominance of lyrical-impressionistic elements and dramatization of the narrative. According to its plot-compositional structure works of the epic-realistic block can be divided into two categories: the first one is determined by the dominance of the linear principle of the beginning, the second one is characterized by the fragmentary principle of composition with the increased aestheticization and intellectualization, in-depth psychological insights, and appeal to “eternal themes”. The works of the lyrical-impressionist model include an internal psychologized plot, attention to feelings and changes in emotional states, as well as stylistic syncretism. The lyrical semantics of the work is closely connected with the position of the lyrical character, personal author's experience. The entire plot of the poem is centered on the inner world of the poetic lyrical character; therefore, it is not the work itself that conveys the plot line but the character’s emotional experiences do that. It is the ability to express a particular feeling, a state without adhering to the plot line that becomes decisive for the dramatized type of story.